Mauritius : Staff Report for the 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
Mauritius aspires to become a high-income country within the current decade. The authorities have laid out a development strategy centered on spurring innovation through skill development, technological upgrading, and improving the ICT infrastructure. Achieving these long-term goals will require macroeconomic stability, reducing risks from declining growth, surging debt, and rising inflation.